Mistaken assumptions drive new Six Sigma model off the road - Westgard, Sten (Array, 2018)
Oosterhuis and Coskun recently proposed a new model for applying the Six Sigma concept to laboratory measurement processes. In criticizing the conventional Six Sigma model, the authors misinterpret the industrial basis for Six Sigma and mixup the Six Sigma “counting methodology” with the “variation methodology”, thus many later attributions, conclusions, and recommendations are also mistaken. Although the authors attempt to justify the new model based on industrial principles, they ignore the fundamental relationship between Six Sigma and the process capability indices. The proposed model, the Sigma Metric is calculated as the ratio CVI/CVA, where CVI is individual biological variation and CVA is the observed analytical imprecision. This new metric does not take bias into account, which is a major limitation for application to laboratory testing processes.Thus, the new model does not provide a valid assessment of method performance, nor a practical methodology for selecting or designing statistical quality control procedures.